Rh disease prevention: the European Perspective. (10th January 2021) - Toly‐Ndour, Cécile; Huguet‐Jacquot, Stéphanie; Mailloux, Agnès; Delaby, Hélène; Canellini, Giorgia; Olsson, Martin L.; Wikman, Agneta; Koelewijn, Joke M.; Minon, Jean‐Marc; Legler, Tobias J.; Clausen, Frederik B.; Lambert, Mark; et al.
Abstract : Background and Objectives: In Europe, postnatal and subsequently antenatal administration of anti‐RH1 (D) immunoglobulins (Ig) has reduced the number of maternal anti‐RH1 immunizations and the incidence of haemolytic disease of the foetus and newborn since the 1960s. Non‐invasive foetal RHD genotyping now enables antenatal prophylaxis to be targeted only to women carrying RHD ‐positive foetus. We aimed at describing how Rh disease prevention is currently managed in different European countries. Materials and Methods: We prepared an online survey on guidelines and biological tests performed for Rh disease prevention. The link was sent to 15 expert laboratories among Europe, selected by their publications in the field. Results: Experts from thirteen countries responded. Guidelines on anti‐RH1 prophylaxis are similar regarding the major aspects of RH disease prevention, including indication and timing of anti‐RH1 Ig administration, as well as indication of foetal RHD genotyping. Different anti‐RH1 Ig preparations are used, and the dosing may differ depending on gestational age. Other controversial issues include (1) timing for foetal RHD genotyping, (2) indication of tests performed to quantitate feto‐maternal haemorrhage prior to anti‐RH1 Ig administration, (3) if there is a remaining indication for newborn RH1 phenotyping. Procedures for monitoring the prophylaxis efficiency and evaluating the national prevention programme also differ among countries. Conclusion: Despite some differences among countries, the Rh disease prevention policies are very efficient in Europe, but HDFN cases due to maternal anti‐RH1 immunization have not completely disappeared. It therefore remains important to share best practices for continuous improvement in reducing anti‐RH1 alloimmunization.